Measurement and modeling of oil slick transport. Issue 10 (22nd October 2016) - Jones, Cathleen E.; Dagestad, Knut‐Frode; Breivik, Øyvind; Holt, Benjamin; Röhrs, Johannes; Christensen, Kai Håkon; Espeseth, Martine; Brekke, Camilla; Skrunes, Stine
Abstract: Transport characteristics of oil slicks are reported from a controlled release experiment conducted in the North Sea in June 2015, during which mineral oil emulsions of different volumetric oil fractions and a look‐alike biogenic oil were released and allowed to develop naturally. The experiment used the Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) to track slick location, size, and shape for ∼8 h following release. Wind conditions during the exercise were at the high end of the range considered suitable for radar‐based slick detection, but the slicks were easily detectable in all images acquired by the low noise, L‐band imaging radar. The measurements are used to constrain the entrainment length and representative droplet radii for oil elements in simulations generated using the OpenOil advanced oil drift model. Simultaneously released drifters provide near‐surface current estimates for the single biogenic release and one emulsion release, and are used to test model sensitivity to upper ocean currents and mixing. Results of the modeling reveal a distinct difference between the transport of the biogenic oil and the mineral oil emulsion, in particular in the vertical direction, with faster and deeper entrainment of significantly smaller droplets of the biogenic oil. The difference in depth profiles for the two types of oils is substantial, with most of the biogenic oil residing below depths of 10 m, compared to the majority of the emulsion remaining above 10 m depth. This difference was key to fitting the observed evolution of the two different types of slicks. Key Points: Mineral oil and biogenic slicks are tracked using L‐band SAR from release until ∼8 h following during a controlled release at sea Simulations fit to the observations are used to refine parameters of an advanced oil transport model Model shows more rapid entrainment and deeper vertical transport of biogenic oil than of emulsions under high wind conditions